PROBLEM OF INTERNATIONALIZATION OF SOCIAL VALUES IN EDUCATION (Education in the 21st Century, 2022)
In order to understand the process of internationalization of that values, cultural stereotypes, etc., we have to observe the features and special conditions of personal communications in education. And vice versa, in which way and with what peculiarities we can organize personal communications for having humanistic values in education system under the requirements of the contemporary world society in the 21st century. Nowadays, in the world system of civil society, all processes (security, safety, healthcare, ecology, education etc.) are united, integrated and attached to each other within different countries and within different nations. And even these nations and states have created common unions for getting better and unique by acquiring effective solutions for global questions and problems for the commonwealth in different ways and in different places, taking into consideration local specifications. In recent decade  the local national and cultural specifications should be taken into special consideration  between societies, creating intercultural and even intersociety spaces.Education, being a part of this general situation and having its own education cohesion areas in the world, aims to be not only a part of research papers, handouts and be on the maps of development strategies, but also have an active enrollment in the solutions of modern challenges and changes, which can have an impact on the development of the society. From this point of view, education implements crucial important role, because all generations are presented in it and they also get influences from more experienced generations and activity models, which can be useful for whole society and future generations in general.
Keywords: Education, Social Values, internationalization, Axiology, Pedagogical Communications